Grafting Enhances Pepper Water Stress Tolerance by Improving Photosynthesis and Antioxidant Defense Systems - Yaiza Gara Padilla; Ramón Gisbert-Mullor; Lidia López-Serrano; Salvador López-Galarza; Ángeles Calatayud (MDPI AG, 2021)
Currently, limited water supply is a major problem in many parts of the world. Grafting peppers onto adequate rootstocks is a sustainable technique used to cope with water scarcity in plants. For 1 month, this work compared grafted peppers by employing two rootstocks (H92 and H90), with different sensitivities to water stress, and ungrafted plants in biomass, photosynthesis, and antioxidant response terms to identify physiological-antioxidant pathways of water stress tolerance. Water stress significantly stunted growth in all the plant types, although tolerant grafted plants (variety grafted onto H92, Var/H92) had higher leaf area and fresh weight values. Var/H92 showed photosynthesis and stomata conductance maintenance, compared to sensitive grafted plants (Var/H90) and ungrafted plants under water stress, linked with greater instantaneous water use efficiency. The antioxidant system was effective in removing reactive oxygen species (ROS) that could damage photosynthesis; a significant positive and negative linear correlation was observed between the rate of CO2 uptake and ascorbic acid (AsA)/total AsA (AsAt) and proline, respectively. Moreover, in Var/H92 under water stress, both higher proline and ascorbate concentration were observed. Consequently, less membrane lipid peroxidation was quantified in Var/H92.